Labor economy: Time factor and efficiency of its use - Nadiya Rud; Iryna Shubala (Економічний форум, 2023)
Conducted research on the time factor. The main goal of the research is to develop an author's approach to the definition of the concept of "time management", to systematize existing methods that help to rationally allocate time between tasks and work, and to increase the efficiency of time use. The relevance of the research is determined by the fact that the effective performance of tasks depends on the correct management of time, because it is a resource that is irreversible, and its irrational use can lead to a decrease in human labor productivity. shows that labor productivity directly depends on the efficiency of use. The systematization of literary sources showed that time management as a mechanism for improving life in modern conditions remains insufficiently studied. It is time management that allows you to develop the ability to manage your time, business and life. The main task of time management is not to have time to do the most, but to do the most important thing - what really needs to be done. In order to effectively use working or personal time, first of all, you need to know what it is spent on and why it is not enough. The process of analyzing the use of time indicates the advantages and disadvantages of time management and allows for the optimal search for time management methods, which will significantly save time resources and increase the efficiency of an individual's work. The methodological toolkit of research methods was the last years of research by leading scientists. The object of research is a person's working time. A large number of potential methods makes it possible to choose the one that is most suitable for everyone. The proposed methods make it possible to harmonize life, to find time not only for fulfilling duties and achieving success in one's career, but also for rest and self-development. The research empirically confirms and theoretically proves that there is a direct relationship between the rational use of time and labor productivity. The results of the research can be useful for the correct distribution of time between various processes, balancing professional and personal activities, and this makes effective use of time one of the important needs of today